EFFICACY OF HAPUSHADI YAPAN BASTI IN JANU SANDHIGAT VATA (KNEE OSTEOARTHRITIS) - Samir, *Girde; Rajendra, Huparikar; Harshad, Gulhane; Amit, Nakanekar; Nilesh, Mahakal; Sunanda, Bhople (International Journal of Ayurveda and Pharma Research, 2016)
Osteoarthritis (OA) is the most common joint disorder. In Ayurveda the disease Sandhigata Vata resembles with OA. Nonsteroidal anti inflammatory drugs (NSAIDS) are mainly prescribed by modern doctors for its treatment. These medicines provide symptomatic relief, but the underlying pathology remains unchecked. Ayurvedic Acharyas have described the application of Bahya Snehan (External oleation), Swedana (fomentation), Abhyantara Tikta Snehapana (medicated ghee), Basti (medicated enema) treatment and Guggulu Prayoga In the management of Sandhigata Vata. Basti is prime treatment for various vata disorders which includes Sandhigat vata. Hapushadi Yapan basti mentioned in Charak siddhisthan for management of various Vata related disorders. Aim: To evaluate the efficacy of Hapushadi Yapan Basti in Sandhigata vata. Materials & Method: In the present study, 30 patients of Sandhigata Vata were given Hapushadi Yapan Basti. Subjective assessment by classical symptoms Sandhi Shoola, Sandhi Shotha, Vatapurna Druti Sparsha, Graha (Restricted movement), Oxford pain chart, WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) index of O.A. for knee by Visual analog scale, Walking time for 10 meters were graded according to their severity. Result: Significant (P<0.05) result were found in all cardinal symptoms of Sandhi Shoola, Sandhi Shotha, Vatapurna Druti Sparsha, Graha (Restricted movement). Conclusion: Hapushadi Yapan Basti was significant in the subjective symptoms of Sandhigata Vata.